Deriving and evaluating alternative antioxidants from corn coproduct proteins - Hu, Ruijia (Kansas State University, 2019)
Corn is one of the most cultivated crops worldwide and is an important source for food, feed and biofuel in the U.S. Corn gluten meal (CGM) and distillers’ dried grains with solubles (DDGS) are two major protein-rich co-products from corn processing, which are potential sources to produce high-value bioactive peptides. However, limited information is available on the production and antioxidant performance of CGM and DDGS protein hydrolysates. The objectives of this study were to produce hydrolysates from those corn co-products via enzymatic hydrolysis, fractionate and identify antioxidant peptides, and evaluate their antioxidant performances with chemical assays and in different model systems. In the first part of our experiment, we screened and evaluated nine different microbial-, plant-, and animal-derived proteases for corn antioxidant production and found that CGM protein hydrolyzed with Neutrase at enzyme-to-substrate ratio of 0.4 Au/g and reaction time of 4 h had the most promising antioxidant properties and yield. The 1-3 kDa ultra-filtrated fraction of the hydrolysate exhibited the highest antioxidant capacities with respect to DPPH and ABTS free radical scavenging activity and metal ion (Fe²⁺) chelating activity. The fraction was further purified through RP-HPLC, and peptide composition and sequences were identified using MALDI-TOF/TOF MS. Addition of this fraction in an oil-in-water emulsion system significantly reduced the amount of primary and secondary oxidation products. It also led to 49.2% reduction of lipid peroxidation compared with the control (i.e., no antioxidant) when incorporated at 1 g/kg in ground pork. In addition, the hydrolysate significantly inhibited cancer cell growth when tested with a human hepatocarcinoma (HepG2) cell model, with cell growth reduction of 64.2% and 71.6% compared with the control (i.e., no antioxidant treatment) when added at 50 and 200 μg/mL, respectively. The second part was focused on enzymatic hydrolysis of CGM using three plant proteases (i.e., papain, ficin, and bromelain) for antioxidant production and process optimization. Optimum enzyme-to-substrate ratios for papain, ficin, and bromelain were found to be 60 U/g, 90 kGDU/g, and 180 kGDU/g, respectively. Optimum hydrolysis time for papain was 3 h, and that for ficin and bromelain was 4 h. The 5-10 kDa peptide fraction produced by papain, <1 kDa fraction produced by ficin, and 3-5 kDa fraction produced by bromelain showed the strongest antioxidant activity and yield in respective hydrolysates. These peptide fractions greatly inhibited lipid oxidation by reducing the formation of thiobarbituric acid reactive substances (TBARS) when added into ground pork. In the last part, hydrolysates were prepared from CGM and DDGS proteins with Neutrase and Alcalase, respectively, and the antioxidant performances of those hydrolysates in bulk oils, ground pork, canine pet food, and pig feed were evaluated by measuring peroxide value (PV) and TBARS. Alcalase-hydrolyzed CGM (CPH-A) and Neutrase-hydrolyzed CGM (CPH-N) had stronger DPPH radical scavenging activity than Alcalase-hydrolyzed DDGS (DPH-A) and Neutrase-hydrolyzed DDGS (DPH-N). CPH-N showed better prevention of lipid oxidation in both corn oil and fish oil compared with other corn antioxidants. The best oxidation prevention in ground meat was observed with 2 g/kg of CPH-N. Lipid oxidation in pet food containing 2% DPH-A was efficiently retarded by 37.8% reduction at the end of incubation, and TBARS value of pig feed containing 2% CPH-N was reduced the most compared with other treatments. This study generates useful knowledge to produce antioxidative hydrolysates from CGM and DDGS, which adds value to the co-products from corn processing industries and provides alternative naturally-derived antioxidant options for food, pet food, and animal feed uses. It revealed that bioactive peptides from corn could inhibit lipid oxidation through scavenging free radicals as well as chelating metal ions. The antioxidants also demonstrated potential anticancer properties based on HepG2 cell study.
Keywords: Bioactive peptide; Protein; Corn coproducts; Enzymatic hydrolysis; Natural antioxidants